THE EFFECT OF PROBLEM BASED LEARNING MODEL ASSISTED BY ANIMATED VIDEOS ON STUDENT LEARNING OUTCOMES IN THE SUBJECT MATTER OF WORK AND ENERGY FOR CLASS X SMA NEGERI 11 MEDAN T.P. 2022/2023 - Besteman Lahagu; Pintor Simamora ((IPER) Indonesian Physics Education Research, 2023)
This study aims to determine the effect of problem-based learning model assisted by animated videos on student learning outcomes in the subject matter of work and energy. This type of research is quasi-experimental  with a two-group pretest-posttest design. The research population was all students of class X MIPA SMA Negeri 11 Medan T.P. 2022/2023 which consists of 7 classes. The sampling were taken by  purposive sampling, the classes taken were class X MIPA 4 as the experimental class and class X MIPA 1 as the control class. The instrument used was a multiple-choice test of learning outcomes in the form of 20 questions and student activity observation sheets. The results showed that the average pretest scores for the experimental class and the control class were 36.83 and 33.83, respectively. The results of testing the hypothesis obtained tcount < ttable, namely 1.4191 <2.002 at the significance level Î± = 0.05 and dk = 58, otherwise h0 is accepted or both classes have the same initial abilities. After implementation, the average post-test score obtained for the experimental class with problem-based learning was 76.8 and the control class with conventional learning was 56. The results of testing the hypothesis obtained tcount (6.35) > ttable (1.671) at the significance level Î± = 0.05, it was stated that ha was accepted meaning there was a difference in student learning outcomes after being given the implementation of problem-based learning model assisted by animated videos on the subject matter of work and energy in class X SMA Negeri 11 Medan.